A importância da alimentação escolar para o processo de ensino aprendizagem na escola municipal de ensino fundamental 17 de Outubro - Pacajá/PA - SANTOS, Orleando Meneses dos (2019)
This article aims to discuss the importance of school feeding for the teaching and learning process of the students of the Municipal School of Elementary Education October 17, located on the Transamazon Highway, BR-230, São Vicente vicinal at Km-294, in the municipality of Pacajá, in the state of Pará. This research had the following question: what factors have caused the constant lack of school feeding for the students of School October 17? It was based on the legislations that ensure students' right to school meals, as well as the works of authors who discuss the subject. The research was based on a qualitative approach, using as data collection technique structured interviews with the subjects that were part of the researched school, which were: two teachers, two parents of students, five students, as well as open questionnaires that were applied for the director of teaching of the rural schools of the municipality of Pacajá, pedagogical coordinator and coordinator of the school lunch of the Secretary of Education. It was verified that the main reason that causes the lack of school feeding for the students is due to the Secretary of Education not to perform the delivery of the food in the school, being under the responsibility of only the teacher. The studies presented here have shown the serious learning losses faced by the students of School October 17 due to the violation of their rights to access to school meals. Considering the authors' reflections on the importance of school feeding for the teaching and learning process, it was possible to perceive how great the losses that the students of the 17 the of October school have faced, regarding the quality of teaching, since the have had little access to school feeding in recent years.